Study on the noise reduction characteristics of porous drainage asphalt mixes considering renewable energy - Qi, Lin; Liu, Jiahao; Liu, Ziang (Archives of Civil Engineering, 2026)
With the increasingly close connection between cities and the rapid development of large highways, this has led to the proportion of traffic noise exceeding the standard section in most cities up to 30% or more, traffic noise pollution has seriously affected people’s quality of life, becoming one of the key issues of current urban pollution. In this study, for the noise reduction characteristics of porous drainage asphalt mixture, the rutting plate specimens and Marshall standard specimens with different gradation, thickness, void ratio and particle size were compared and tested by Marshall method. The test results show that the peak absorption coefficient of Porous Asphalt Concrete 13 (PAC-13) is 0.67, the average absorption coefficient is 0.3, and the noise reduction coefficient is 0.32. From the perspective of noise reduction coefficient, the value of PAC-13 is 2.46 times that of Asphalt Concrete 13(AC-13) and 1.88 times that of Stone Mastic Asphalt 13 (SMA-13). Its comprehensive noise reduction and sound absorption ability is far better than SMA-13 and AC-13. The smaller the particle size of the PAC specimen, the stronger its sound absorption capacity. The test results are in line with expectations and have some reference value for the study of urban noise pollution. The study conducted in-depth research on the noise reduction performance of commonly used asphalt materials in recent years, which provided strong support for pavement laying and urban noise reduction research.
Keywords: traffic noise; porous drainage asphalt; noise reduction characteristics; PAC-13